2005
DOI: 10.1074/jbc.m412476200
|View full text |Cite
|
Sign up to set email alerts
|

Double-spanning Plant Viral Movement Protein Integration into theEndoplasmic Reticulum Membrane Is Signal Recognition Particle-dependent,Translocon-mediated, andConcerted

Abstract: The current model for cell-to-cell movement of plant viruses holds that transport requires virus-encoded movement proteins that intimately associate with endoplasmic reticulum membranes. We have examined the early stages of the integration into endoplasmic reticulum membranes of a double-spanning viral movement protein using photocross-linking. We have discovered that this process is cotranslational and proceeds in a signal recognition particle-dependent manner. In addition, nascent chain photocross-linking to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 35 publications
(50 reference statements)
2
55
1
4
Order By: Relevance
“…More recently, we have demonstrated that the protein integrates into the ER membrane cotranslationally through the Sec61 translocon 13 . But in contrast to what has been observed for other double-spanning proteins both in mammalian and prokaryotic systems 15; 16 , p9 remained adjacent to Sec61α until translation was terminated.…”
Section: Plant Viral Membrane Protein P9 Is Sequentially Adjacent To mentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, we have demonstrated that the protein integrates into the ER membrane cotranslationally through the Sec61 translocon 13 . But in contrast to what has been observed for other double-spanning proteins both in mammalian and prokaryotic systems 15; 16 , p9 remained adjacent to Sec61α until translation was terminated.…”
Section: Plant Viral Membrane Protein P9 Is Sequentially Adjacent To mentioning
confidence: 99%
“…A quantitative comparison of the relative amounts of photoadducts containing Sec61α and TRAM was made by splitting each sample and then immunoprecipitating in parallel one half with an affinity-purified antiserum specific for Sec61α 13 and the other half with an affinity-purified antiserum for TRAM. When the probe was positioned in TM1, fewer crosslinks were formed to TRAM than to Sec61α, but the number of TRAM photoadducts increased with increasing RNC lengths (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In viruses with genomes that include three partially overlapping open reading frames, termed the triple-gene block (TGB), all three TGB proteins are required for movement where the two smaller proteins, TGBp2 and TGBp3, are also TM proteins (24). Furthermore, cross-linking experiments with carnation mottle virus p9 protein demonstrated that its membrane insertion occurs cotranslationally in a signal recognition particle-dependent manner and throughout the cellular membrane integration components, the translocon (33,34).…”
mentioning
confidence: 99%
“…In this regard, two TM segments have been found to accumulate within or adjacent to the translocon before final integration into the lipid bilayer. [39][40][41][42][43] Furthermore, molecular dynamics simulations of the translocon in a fully solvated lipid bilayer showed that two helices can coexist within the translocon (J. Gumbart, personal communication). An interesting possibility arising from these observations is that the translocon may facilitate membrane protein integration by allowing efficient polar interactions between consecutive TM segments harboring charged residues and thereby stabilizing them in the nascent polypeptide.…”
Section: Discussionmentioning
confidence: 99%